1985
DOI: 10.1176/ajp.142.6.741
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder, hypnotizability, and imagery

Abstract: Twenty-six Vietnam veterans were studied to determine the relationship between posttraumatic stress disorder and hypnotizability. The intensity of their posttraumatic stress disorder was measured by a self-report. Their hypnotizability scores, vividness of imagery scores, and symptomatic profiles were also ascertained. Veterans with low or no posttraumatic stress disorder scores had normal hypnotizability scores and normal imagery scores, whereas those with high posttraumatic stress disorder scores had high hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(13 citation statements)
references
References 11 publications
0
12
0
1
Order By: Relevance
“…Only a few studies have assessed the relation between imagery ability and PTSD symptoms. These clinical studies indicated that better imagery capacities coincided with more PTSD symptomatology ( Stutman and Bliss, 1985 ) and more flashbacks and nightmares ( Bryant and Harvey, 1996 ).…”
Section: Introductionmentioning
confidence: 96%
“…Only a few studies have assessed the relation between imagery ability and PTSD symptoms. These clinical studies indicated that better imagery capacities coincided with more PTSD symptomatology ( Stutman and Bliss, 1985 ) and more flashbacks and nightmares ( Bryant and Harvey, 1996 ).…”
Section: Introductionmentioning
confidence: 96%
“…Respecto a los trastornos relacionados con el trauma, estudios clínicos han encontrado relaciones positivas entre hipnotizabilidad con estrés agudo (Bryant, Guthrie y Moulds, 2001), estrés postraumático y sintomatología disociativa (Bryant, Guthrie, Moulds, Dixon y Felmingham, 2003;DuHamel, Difede, Foley y Greenleaf, 2002;Frischholz, Lipman, Braun y Sachs, 1992;Putnam, Helmers, Horowitz y Trickett, 1995;Roelofs et al, 2002;Spiegel, Hunt y Dondershine, 1988;Stutman y Bliss, 1985).…”
Section: N F O R M a C I ó N D E L A R T í C U L O Historia Del Artunclassified
“…Although patients with DID have higher hypnotizability than those with other mental disorders, higher hypnotizability is also found in patients with chronic refractory post-traumatic states in general 5456. Hence, data are required to determine the degree it represents a diathesis for DID that may reflect part of the biological contribution to the development of the disorder in the presence of other necessary factors.…”
Section: Developmental Traumatizationmentioning
confidence: 99%